PENGARUH PERSEPSI, MOTIVASI, MINAT, DAN PENGETAHUAN TENTANG PAJAK MAHASISWA PROGRAM STUDI AKUNTANSI UNIVERSITAS NUSA CENDANA TERHADAP PILIHAN BERKARIR DI BIDANG PERPAJAKAN - Johanes V. A. A. Koa; Karmila Dwi Lestari Mutia (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2021)
The purpose of this study was to determine the effect of perceptions, motivations, interests, and knowledge of student taxes on career choices in taxation, either partially or simultaneously. This research was conducted at the Accounting Study Program, University of Nusa Cendana. The sampling technique in this study used a purposive sampling technique. The population is 892 students and the research sample is 100 students. The results of this study indicate that the perception, motivation, and interest of students in the Accounting Study Program at the University of Nusa Cendana has an effect on the choice of a career. in the field of taxation, knowledge of taxes by students of the Accounting Study Program at the University of Nusa Cendana has no effect on career choices in taxation. Perceptions, motivations, interests, and knowledge of taxes simultaneously affect the choice of a career in taxation.